2010
DOI: 10.1096/fj.10-168294
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform activity interferes with proteolytic processing of Reelin required for dentate granule cell positioning

Abstract: The extracellular matrix protein Reelin is an essential regulator of neuronal migration and lamination in the developing and mature brain. Lack of Reelin causes severe disturbances in cerebral layering, such as the reeler phenotype and granule cell dispersion in temporal lobe epilepsy. Reelin is synthesized and secreted by Cajal-Retzius cells and GABAergic interneurons, and its function depends on proteolytic cleavage after secretion. The mechanisms regulating these processes are largely unknown. Here, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 45 publications
10
66
1
Order By: Relevance
“…We cannot rule out the possibility that even though the density of neurons is similar in the autistic and control cerebral cortex, individual neurons may produce or secrete lower amounts of RELN protein in the cerebral cortex of autistic subjects. The decrease of the amount of Reelin reported in autism could also result from abnormal RELN processing in RELN+ neurons leading to a lack or decreased synthesis and/or secretion of RELN, as has been shown for other conditions [29,30]. Nevertheless, Fatemi et al showed that not only the 410 kDa RELN isoform is decreased in human cortical areas associated to autism, but also the 330 kDa and 180 kDa isoforms, as well as RELN mRNA levels.…”
Section: Discussionmentioning
confidence: 91%
“…We cannot rule out the possibility that even though the density of neurons is similar in the autistic and control cerebral cortex, individual neurons may produce or secrete lower amounts of RELN protein in the cerebral cortex of autistic subjects. The decrease of the amount of Reelin reported in autism could also result from abnormal RELN processing in RELN+ neurons leading to a lack or decreased synthesis and/or secretion of RELN, as has been shown for other conditions [29,30]. Nevertheless, Fatemi et al showed that not only the 410 kDa RELN isoform is decreased in human cortical areas associated to autism, but also the 330 kDa and 180 kDa isoforms, as well as RELN mRNA levels.…”
Section: Discussionmentioning
confidence: 91%
“…N-t cleavage is catalyzed by an unidentified metalloprotease(s) that bind(s) heparin (10). Abnormal N-t cleavage has been implicated in Alzheimer disease (41) and epilepsy (42). Recent studies from our laboratory and other laboratories indicate that a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) 4 is able to cleave Reelin at the N-t site (43,44), although its contribution to Reelin metabolism in vivo remains uncertain.…”
mentioning
confidence: 99%
“…Reelin is a relatively large, secreted glycoprotein that integrates into the extracellular matrix (see [92] for review). It is most probably released by constitutive, depolarization-independent pathways [87]. The canonical receptors for reelin are VLDLR (very low density lipoprotein receptor) and ApoER2 (apolipoprotein E receptor 2), which activate various molecular downstream targets via the adaptor protein Dab1 [36,37].…”
Section: Excurse 1: Reelinmentioning
confidence: 99%